Solar Energy Modeling and Mapping for the Sustainable Campus at Monash University - Radosevic, Nenad; Liu, Gang-Jun; Tapper, Nigel; Zhu, Xuan; Sun, Qian (Chayn) (Frontiers in Sustainable Cities, 2022)
An increase in energy demands and positive public acceptance of clean energy resources have contributed to a growing need for using solar energy in cities. Solar photovoltaic (PV) deployment relies on identifying locations with high solar energy potential. In urban context, building rooftops are often the most available and suitable for installation of solar PV panels. In this work, we demonstrate a new geospatial method for spatiotemporal modeling and mapping of solar energy potential based on a high-resolution (0.2m) digital surface model (DSM) and solar radiation dataset. The assessment identifies building rooftops with high solar energy potential in the study area. It shows variation in solar energy potential for different rooftop orientation and geometry. The results from the assessment are validated using recorded energy output data from four solar PV systems in the study area. The method can be used for decision making support in planning and development of solar energy systems in any urban environment.